Cosmopolitanism as a Concept and a Social Phenomenon - Gizatova, Gulnaz K.; Ivanova, Olga G.; Gedz, Kirill N. (Journal of History Culture and Art Research, 2017)
The article is devoted to cosmopolitanism as a concept and a social phenomenon. The authors believe that cosmopolitan ideas and mentality are a necessary manifestation of modern globalization processes. Cosmopolitanism as a pattern of public consciousness reflects the essential features of modern social processes. At the same time, the very idea of cosmopolitanism is contradictory, multifaceted, and therefore it cannot be considered only within the framework of categorical opposition "local - global". That is why this research is carried out dialectically: from the point of view of the contradictory unity of the cosmopolitanism's objective manifestations and the diverse interpretations of this phenomenon. Considering a wide range of approaches in studies of the cosmopolitanism phenomenon prevailing in modern social theory, the authors emphasize the need for its comprehensive philosophical interpretation. In addition, referring to the historical overview of cosmopolitan ideas, the authors come to the conclusion that further studies of cosmopolitanism should be based on an interdisciplinary approach. Particular attention in this article is paid to a couple of "cosmopolitanism" and "patriotism" categories. The main conclusion of the article is that it is cultural cosmopolitanism as a concept and social phenomenon that can clarify the essential contradictions in modern social processes.